IMPLEMENTASI JEJARING BISNIS STRATEGIS DALAM RANGKA MENINGKATKAN KEGIATAN EKSPOR SEKTOR BISNIS MIKRO DI JAWA TENGAH - Hari Susanta Nugraha; Sovy Rahma Diffa (POLITEKNIK LP3I JAKARTA, 2024)
Developing business networks in international markets by carrying out export activities can encourage the acceleration of the country's economy, which is currently being assisted by the FTA Center from the Indonesian Ministry of Trade. The aim of the FTA Center is to provide a public service to micro and small business actors in terms of carrying out export activities by providing assistance regarding export procedures. Thus, the FTA Center plays an important role in developing international business networks to promote or be able to increase export numbers in Indonesia. This type of research is descriptive with a qualitative approach. The research results show that there has been an increase in the number of exporters with a total of 42 times from micro business actors using export assistance service facilities. From the results of this research, the FTA Center, especially in Semarang City, has succeeded in carrying out its role as a partner for MSMEs by becoming an international business network in implementing free trade agreements. Thus, to improve the work achievements of the Semarang FTA Center, an approach using social media is needed to provide outreach services related to free trade agreements. Keywords: Business Network, Free Trade Agreement, FTA Center